Supporting Capabilities: Using Psychosocial Concepts to Guide a Sennian Approach to Escaping Urban Poverty - Burgess, Rochelle (Consilience, 2014)
Currently, more than half of the human population resides in cities. Over one-third of these cities are located in the global south, where many of the world's slum and squatter settlements are located. The unique experience of the urban poor has helped initiate a reconfiguration of poverty definitions, led by Amartya Sen's capabilities approach. Countless poverty alleviation programs have since incorporated his ideals, but with limited success. This paper attempts to address these issues by examining the role of psychosocial phenomena such as identity, social representations and stigma in the escape from poverty. Through unpacking the interactions between these phenomena against the background of poverty within Brazilian favelas, the author attempts to help inform a more concrete framework for the application of Sennian approaches to poverty alleviation in urban centers.